Exploring Health Informatics for Chronic Disease Management: A Systematic Review of Tools and Outcomes - Alanazi, Eman Shukhair Suliman; Alenezi, Mona Sanad Khudair; Alenezi, Mai Fahad Muqbel; Albarrak, Suad Ibrahim Rubaiean; Aghithi, Afrah Saud Musabeh; Alenzi , Amal Fayadh; Alshammeri, Monifah Romeh Mfdi; Alshammeri , Ajayb Shafi; Alenazy, Asma Mohammed; alfaisal, Nahla saleh (Journal of Ecohumanism, 2024)
Chronic diseases represent a significant burden on healthcare systems worldwide, necessitating innovative approaches to enhance patient management and improve health outcomes. Health informatics tools, including electronic health records (EHRs), mobile health applications, telemedicine, and predictive analytics, offer promising solutions for managing chronic conditions by facilitating patient engagement, supporting clinical decision-making, and improving healthcare efficiency. This systematic review evaluates recent literature on health informatics tools used in chronic disease management, examining their impact on patient health outcomes, adherence, and healthcare delivery efficiency. Findings reveal that digital health solutions, particularly mobile health applications and remote monitoring technologies, demonstrate substantial benefits in improving patient engagement and adherence to treatment protocols, leading to better disease management and reduced hospitalization rates. However, challenges such as data privacy, interoperability, and limited digital literacy remain significant barriers to widespread implementation. This review highlights the need for continued research to optimize health informatics applications, address implementation challenges, and further integrate these tools into healthcare systems for improved chronic disease management.